2015
DOI: 10.1039/c5ta05095b
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic generation of graphene beads for supercapacitor electrode materials

Abstract: Three-dimensional (3D) solid or hollow graphene beads (GBs) with an obvious crumpled surface were fabricated by using a microfluidic emulsification device and employed as electrode materials for supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…Commonly, electrodes for supercapacitor applications employ micrometer-sized particles of nanoporous carbon consolidated by the use of polymer binder. , To further enhance the power performance via fast ion transport, sub-micrometer particles are of high interest. For example, using an emulsion synthesis process, we have recently shown the superior rate handling ability of sub-micrometer carbide-derived carbon (CDC) beads with diameters ranging from 20 to 200 nm . This aligns with the enhanced performance of nanometer-sized TiC powders, which demonstrate an enhanced power rating compared to their micrometer-sized counterparts .…”
Section: Introductionmentioning
confidence: 89%
“…Commonly, electrodes for supercapacitor applications employ micrometer-sized particles of nanoporous carbon consolidated by the use of polymer binder. , To further enhance the power performance via fast ion transport, sub-micrometer particles are of high interest. For example, using an emulsion synthesis process, we have recently shown the superior rate handling ability of sub-micrometer carbide-derived carbon (CDC) beads with diameters ranging from 20 to 200 nm . This aligns with the enhanced performance of nanometer-sized TiC powders, which demonstrate an enhanced power rating compared to their micrometer-sized counterparts .…”
Section: Introductionmentioning
confidence: 89%
“…17,18 The 3D geometric structure of graphene could be fabricated by various methods, including self-assembly, 19,20 additive manufacturing, sol–gel methods, 21 electrostatic spinning, 22 and microfluidics. 23,24 Ma et al 25 fabricated porous graphene gels based on a combined sol–gel and hydrothermal method for methylene blue (MB) adsorption. An adsorption capacity as high as 192 mg/g of the ultralight reduced-graphene oxide gels is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the intensity ratio of D band to G band (I D /I G ) revealed the disorder degree of carbon materials. 48 The I D /I G values of MCNTBs before and aer calcination clearly showed that the D/G intensity ratio aer calcination (I D /I G ¼ 1.41) was higher than that of the beads without treatment (I D /I G ¼ 1.27), indicating a decrease in the average size of sp 2 domains. 49 The FTIR spectra are given to characterize the functional groups of MCNTBs before and aer calcination (Fig.…”
Section: Characteristics Of Magnetic Porous Mcntbsmentioning
confidence: 93%